A passive multiple trailer system with off-axle hitching - Lee, JH; Chung, WJ; Kim, MS; Song, JB (INST CONTROL ROBOTICS & SYSTEMS, KOREAN INST ELECTRICAL ENGINEERS, 2004)
This paper deals with the design and control of passive multiple trailer systems for practical applications. Due to the cost and complexity of the trailer mechanism, passive systems are preferred to active systems in this research. The design and control objective is to minimize the trajectory tracking errors occurring in passive multiple trailers. Three sorts of passive trailer systems, off-hooked, direct-hooked, and three-point, are discussed in this paper. Trajectory tracking performance and stability issues under constant curvature reference trajectories are investigated for these three types. As well, various simulations and experiments have been performed for each type. It is shown that the proposed off-hooked trailer system produces a tracking performance that is superior to the others.